ANALISIS PENGARUH QUICK RATIO, LEVERAGE DAN RASIO AKTIVITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Dalam Kurun Waktu 2018-2020) - Nurfaizah, Nurfaizah; Pamungkas, Leo Dadyo (Journal Competency of Business, 2022)
The value of the company is one of the considerations of investors before deciding to provide funds to the company. This study aims to determine the effect of Quick Ratio, Leverage and Activity Ratio on firm value.This study uses a descriptive quantitative approach with a sample using purposive sampling technique. This research was conducted using the documentation method using annual financial report data for companies listed on the Indonesia Stock Exchange (IDX). The data analysis method used is multiple regression analysis. The sample used in this study amounted to 34 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The results of this study indicate that, (1) Quick Ratio has a positive influence on firm value, this is indicated by a significant value of 0.022 which means it is smaller than = 0.05 with a coefficient value of 1.194. (2) Leverage (DER) has a positive effect on firm value, this is indicated by a significant value of 0.007 which means it is smaller than = 0.05 with a coefficient value of 0.687. (3) Activity Ratio (TATO) has a negative effect on firm value, this is indicated by a significant value of 0.015 which means it is smaller than = 0.05 with a coefficient value of -1.860.